PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP RESUME BERBASIS STRATEGI TRUE OR FALSE TERHADAP HASIL BELAJAR GEOGRAFI KELAS XI DI SMA N 4 PAYAKUMBUH - Pratama, Afil Putra; Nova, Sari (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study aims to determine the effect of the Group Resume type cooperative learning model based on the True or False strategy on the learning outcomes of class XI geography at SMAN 4 Payakumbuh. This type of research is quantitative, with a total sample of 68 students. Data collection techniques in the form of questionnaires, learning outcomes tests, and documentation. Meanwhile, for data processing using individual completeness, Normality Test, Homogeneity Test along with T-Test. Based on the effectiveness analysis using N-Gain, the effective results for the experimental class are 73% which falls into the category of quite effective, while for the control class the results are 53% where which is less effective, it can be interpreted that the implementation of the Group Resume model based on the True or False strategy is quite effective compared to the conventional model. Based on the Determinant Test, there is a simultaneous influence between the Group Resume and True or False variables which can explain the learning outcomes variable by 80%, meaning that the Group resume and True or False variables can affect student learning outcomes by 80%